A cooling cuff compared to a moist ice pack on radial artery blood flow and lumen diameter in healthy participants - Joshua Gernetzky; Laura O'Connor; Desiree Varatharajullu; Zombuso C. Dludla (AOSIS, 2018)
Background: Cryotherapy is a favourable treatment for post-traumatic injuries in the acute stage because of its effect on inflammation and pain. A novel cooling cuff, which can be easily used and can be wrapped around the injured area that does not require freezing, has been developed. Its efficacy compared to traditional ice therapy has not been established. Aim: To establish the effect of a cooling cuff on radial artery blood flow and lumen diameter compared to moist ice. Setting: Chiropractic clinic and radiographic laboratory. Method: A controlled laboratory pre-test post-test investigation assessed asymptomatic participants who were randomly allocated into a moist ice pack (n = 22) or the cooling cuff (n = 21) group. The intervention was placed on the participants forearm over the radial artery for 15 min. Data was collected by a qualified diagnostic radiographer using Doppler ultrasound. Data was analysed, using repeated measures analysis of variance to assess changes in blood flow and lumen diameter pre- and post-intervention. A p-value of less than 0.05 was considered significant. Results: Both groups showed a significant decrease in radial artery blood flow (p < 0.001) after 15 min with no significant changes being observed in diameter size. No significant differences were observed between the groups for radial artery blood flow or diameter. Conclusion: The cooling cuff resulted in a similar effect on radial artery blood flow and lumen diameter as moist ice, indicating that patients and practitioners may utilise the cooling cuff in the acute phases of an injury to alter blood flow.